Рок-звезда: [роман] / Джекки Коллинз ; пер. с англ. А. П. Романов - Коллинз Джекки (Интрига, 1996)
Экземпляры: (20190313) / Инвентарный номер: 34198 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: К 60 / ББК: 84(7Сое)